2005
DOI: 10.1007/s00449-005-0421-5
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion cultures of human embryonic stem cells

Abstract: Human embryonic stem cells (hESC) are self-renewing pluripotent cells capable of differentiating into cells representative of all three embryonic germ layers. Hence, they hold great potential for regenerative medicine. However, significant cell numbers are required to fulfill their potential therapeutic applications. In this study, perfusion with supplemented conditioned media (SCM), produced by mouse embryonic fibroblasts (MEF), was adopted to improve cell densities of hESC cultures. Perfusion enhanced hESC n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 18 publications
(20 reference statements)
1
32
1
Order By: Relevance
“…It has been shown that medium perfusion is beneficial even in 2D cultures [Fong et al, 2005]. Perfusion facilitates continuous nutrient and oxygen supply [Ouyang and Yang, 2008] in larger cell masses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that medium perfusion is beneficial even in 2D cultures [Fong et al, 2005]. Perfusion facilitates continuous nutrient and oxygen supply [Ouyang and Yang, 2008] in larger cell masses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cormier et al attributed the decline in viability of mESC aggregates after 6 days in batch culture to the associated build-up of ammonia (to 2.5 mM) and decrease in pH (from 7.6 to 6.6) [15]. Perfusion, frequent feeding, and/or the use of gas-permeable culture surfaces increased the expansion of MSCs [4,5,6•], ESCs [32,33] and mammary epithelial stem cells [12], while retaining stem cell potential [5,9,32,33]. Under conditions for which oxygen was not limiting, Zhao et al reported greater human MSC expansion at a lower perfusion rate [7].…”
Section: Perfusionmentioning
confidence: 99%
“…Understanding the mechanisms of hESC self-renewal and proliferation as non-differentiated cells would greatly facilitate the establishment of defined derivation and culture conditions for hESC (Vallier et al 2005, Wang et al 2005a, Armstrong et al 2006, Rho et al 2006. Recent advantages in the use of biomaterials (Anderson et al 2004) and perfusion culture systems (Fong et al 2005) for the culture of hESC suggest that large-scale culture of hESC in bioreactors under controlled environment using defined culture medium and biomaterial substrates may be feasible in future.…”
Section: Defined Quality Cells Also Needed For Research Purposesmentioning
confidence: 99%